2019
DOI: 10.1002/hpja.295
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes coverage in Australian newspapers (2013‐2017): A computer‐based linguistic analysis

Abstract: Issue addressed: This study analysed diabetes coverage in 12 Australian metropolitan/national newspapers over a period of 5 years (2013-2017). It aimed to describe quantitative tendencies in diabetes coverage (amount of articles per newspaper and over time) and to identify potential discrepancies between diabetes coverage and societal prevalence of diabetes. The study addressed the following research questions, with a focus on language use: • How frequent are mentions of different types of diabetes? • How are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…and 117 other items (opinion, profiles, personal recounts, etc). More information about the construction of the dataset, called Diabetes News Corpus (DNC), is provided in Bednarek and Carr (2019a, b).…”
Section: Introductionmentioning
confidence: 99%
“…and 117 other items (opinion, profiles, personal recounts, etc). More information about the construction of the dataset, called Diabetes News Corpus (DNC), is provided in Bednarek and Carr (2019a, b).…”
Section: Introductionmentioning
confidence: 99%
“…A significant body of work which applies linguistics to scientific and health matters was published in 2020. For example, Deignan and Semino (2020) focus on the metaphors used to discuss climate change in educational material and in interviews with secondary school pupils in the UK and Bednarek and Carr (2020) conduct a computer-based analysis of diabetes coverage in Australian newspapers. Coffey-Glover (2020) uses feminist discourse analysis to investigate the online language of ‘exclusive pumpers’, women who express breastmilk as an alternative to breast feeding or using formula.…”
Section: Discourse and Multimodalitymentioning
confidence: 99%
“…As a first step, the alphabetically-sorted DNC word list was consulted to identify any potential references to Aboriginal and Torres Strait Islander people(s) and matters-as briefly summarised in [21] and elaborated on here. As a reminder, a word list is based on the occurrence of single forms; that is, it will list Torres, Strait, and Islander separately.…”
Section: Frequency and Rangementioning
confidence: 99%
“…This research does argue, however, that 'the language used by the media in communicating about diabetes has the potential to influence general perceptions and attitudes about diabetes in a whole spectrum of people, not just those people living with diabetes but also their spouses, friends, parents, and significant others' [20, p. 493]. Another study [21], which this article builds on and extends, only reported the low number of references to Aboriginal and Torres Strait Islander people(s) or matters in diabetes coverage alongside other project results (described in more detail below in 'Frequency and range'). There is a general paucity of research on Australian media representations of Indigenous health [9,17], especially in relation to language use.…”
Section: Introductionmentioning
confidence: 96%